Chemical, sensory, and microbiological stability of stored raw peanuts packaged in polypropylene ventilated bags and high barrier plastic bags - Martín, María Paula (2016)
The purpose of this study was to compare the chemical, microbiological, and sensory stability of rawpeanuts packaged in high barrier plastic bags (EVOH) under vacuum and in regular polypropylene (PP)ventilated bags during 60 days of storage at 40 C. The peroxide value showed a higher increase (from0.38 to 0.95 meqO2/Kg) in PP samples than in EVOH samples (from 0.38 to 0.63 meqO2/Kg) duringstorage. The highest free fatty acids value (0.60g oleic acid/100g peanut oil) was reached by EVOHsamples at day 60. The samples packaged in PP pouches showed a significantly higher oleic/linoleic ratio(15.94) and lower iodine value (78.07) with respect to EVOH (13.80 and 80.30, respectively) at the end ofstorage. A greater decrease of a-tocopherol was observed in PP ventilated bags (from 27.78 to 23.24 mg/100g oil) than in EVOH bags (from 27.78 to 25.10 mg/100g oil). At storage day 60, only molds weredetected for both peanut samples but EVOH (2900 CFU/g) showed higher values than PP (2170 CFU/g). Anincrease of the cardboard flavor and a decrease of roasted peanutty were greater in PP samples. TheEVOH bags preserve raw peanuts with better quality in comparison with PP bags.